HAZOP-Based Radiological Risk Assessment of Pebble Bed Fuel Handling Systems - Kurniawan, Rusbani; Ekaranti, Egnes; Rachman, Agus Nur; Nugraha, Eka Djatnika; Ngarayana, I Wayan; Djunaidi, Zulkifli (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
The High-Temperature Gas-Cooled Reactor (HTGR), a promising candidate for Generation IV nuclear reactors, boasts superior inherent passive safety features and a continuous fuel handling system. This system employs multi-pass cycles, utilizing pneumatic and gravitational mechanisms to feed, circulate, and unload the pebble bed fuel element. This paper presents a descriptive analysis assessing the safety risk of the fuel handling system design in HTR-10. The Hazard and Operability Study (HAZOP) methodology is employed to identify hazard parameters, deviation limitations, causes, impacts, and potential risks to the system’s main components. The establishment of probability scales, consequence criteria, risk level ratings, and control activities adheres to the ISO 31000 standard. Primary data were gathered through expert interviews, while secondary data were sourced from design layout documentation, literature reviews, and safety analysis reports. Six main components - the elevator, core, singulator, failed fuel separator, burnup measurement, and distributor - were selected as assessment nodes from the piping and instrumentation diagram. The assessment revealed that each node initially presented a moderate to extreme risk potential (risk level rating C to E). However, after applying the effectiveness index of the designed control, the residual risk for all nodes was reduced to an acceptable limit (risk rating A - very low). Therefore, the fuel handling system design already incorporates adequate control activities to mitigate potential safety risks due to system component failure. As safety risk assessment is dynamic, it should be reviewed periodically or whenever there are design changes at any project stage. This ensures the safety risk magnitude is consistently known and managed effectively.